A Note on the Wage Effects of the 1972 Raising of the School Leaving Age in Scotland and Northern Ireland. (2nd August 2018) - Buscha, Franz; Dickson, Matt
Abstract: In this note, we use the UK Labour Force Survey to estimate the wage return to an additional year of schooling for Scotland and Northern Ireland exploiting the 1972 Raising of the School Leaving Age (RoSLA). Prior literature on this topic has consistently ignored both countries in a UK context, likely due to an incorrect belief that they were not affected by the 1972 RoSLA until some years later. We demonstrate that both countries were affected by the education reform in 1972 and our estimates suggest a positive effect on hourly wages for Scotland.